Periodontal health status among chronic obstructive pulmonary disease with age- and gender-matched controls - Dantala Satyanarayana; Suhas Kulkarni; Dolar Doshi; Madupu Padma Reddy; Sana Khaled; Adepu Srilatha (Wolters Kluwer Medknow Publications, 2023)
Background: Periodontal disease and chronic obstructive pulmonary disease (COPD) share a pathogenic mechanism that involves activating and using inflammatory cytokines and neutrophils, which generate pathological changes in various tissues with a chronic degenerative outcome. Aim: the aim of this study was to assess and compare the periodontal health status among COPD patients with age- and gender-matched controls. Materials and Methods: All the patients aged >30 years who were diagnosed with COPD by the physician were included as cases, while people who are apparently healthy and age and gender matched with cases were included as controls. Data on demographic details, socioeconomic status (Kuppuswamy scale), deleterious oral habits, and oral hygiene practices were obtained. The Simplified Oral Hygiene Index (OHI-S) and the WHO basic oral health survey proforma (1997) were used to obtain the data on oral hygiene and periodontal status respectively. Results: Most cases had moderate COPD severity (58.25%). The overall mean OHI-S, CPI, and LOA were higher among cases (3.92 ± 0.95, 3.68 ± 0.60, and 2.33 ± 1.10, respectively) in comparison to controls. Further, among cases, the mean oral hygiene and periodontitis increased with increased severity of COPD. Although among both cases and controls, gender, tobacco use, and alcohol consumption influenced their periodontal status, significant odds of higher risk were seen only among cases. Further, subjects with COPD had higher odds of having poor oral hygiene, deeper pocket depths, and LOA. Conclusion: A strong association between COPD and periodontitis was observed. The oral hygiene and periodontal disease worsened with the severity of COPD.